2016
DOI: 10.1080/07315724.2015.1113902
|View full text |Cite
|
Sign up to set email alerts
|

White Rice Consumption, Body Mass Index, and Waist Circumference among Iranian Female Adolescents

Abstract: There was significant association between rice consumption and obesity as well as diet quality indices among Iranian adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
4
0
1
Order By: Relevance
“…Despite the consumption of rice concomitantly with beans has been consistently associated with healthier eating patterns [ 50 , 51 ], favorable weight outcomes in an 18-month randomized trial [ 52 ], and reduced BMI and waist circumference in low-income Brazilian women [ 53 ], studies indicate that the benefits of this pattern occur mainly because the intake of beans [ 42 , 54 ]. In accordance with our findings, other studies found a positive association between excess body weight and rice intake [ 42 , 55 ], but not with beans after adjusting for the highly-correlated and sizable rice intake [ 42 ], as we observed here. A study with 675 consumers in a restaurant serving buffet-by-weight also observed association between large portion size and EBW, even in consumers of rice and beans [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the consumption of rice concomitantly with beans has been consistently associated with healthier eating patterns [ 50 , 51 ], favorable weight outcomes in an 18-month randomized trial [ 52 ], and reduced BMI and waist circumference in low-income Brazilian women [ 53 ], studies indicate that the benefits of this pattern occur mainly because the intake of beans [ 42 , 54 ]. In accordance with our findings, other studies found a positive association between excess body weight and rice intake [ 42 , 55 ], but not with beans after adjusting for the highly-correlated and sizable rice intake [ 42 ], as we observed here. A study with 675 consumers in a restaurant serving buffet-by-weight also observed association between large portion size and EBW, even in consumers of rice and beans [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…In Iran, where this study was conducted, the most important component of the traditional diet is refined grains 80 . Refined grains contain lower amounts of dietary fibre, magnesium, vitamin E, and phytoestrogens since the bran and germ of the grains are removed 80,81 . Data show that Iranian people consumption of refined grains is among the highest levels in the world, while dietary intakes of fibres, fruits, vegetables, legumes, and nuts are lower than the recommendations of the Food Guide Pyramid 80 .…”
Section: Discussionmentioning
confidence: 99%
“…80 Refined grains contain lower amounts of dietary fibre, magnesium, vitamin E, and phytoestrogens since the bran and germ of the grains are removed. 80,81 Data show that Iranian people consumption of refined grains is among the highest levels in the world, while dietary intakes of fibres, fruits, vegetables, legumes, and nuts are lower than the recommendations of the Food Guide Pyramid. 80 Moreover, fruit juices do not have the proportion of dietary fibre of the whole fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The association study represented that the over-intake of cereal was positively associated with higher weight categories, while deficient consumption of cereal contributed to a lower risk of having high BMI values. Previous studies also indicated that refined grain and wheat, which comprised up to 90% of the staple food in the CDG 2016, were strongly associated with obesity [ 25 , 26 ]. The associations between intake of vegetables with adiposity were concordant with previous studies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%